Clinical Pharmacist Role in Estimation And Evaluation of Treatment Outcomes in Patients Suffering with Respiratory Tract Infections in A Tertiary Care Teaching Hospital (Indian Journal of Public Health Research & Development, 2020)
The primary function of the respiratory system is to oxygenate blood and eliminate carbon dioxide, whichrequires that blood come into virtual contact with fresh air to facilitate diffusion of respiratory gases betweenblood and gas. It refers to any number of infectious diseases involving the respiratory tract. Materials and Methods: Place of Study: The study is carried out in patient “Department of Pulmonology” IP at NarayanaHospitals, Nellore, collaborated with a 1440 bedded multidisciplinary hospital.Results: Demographic details of the patient was collected and presented as results in the data.Discussion: In our study total of 405 patients 360 are willing to provide the information of age group 20-60and which the maximum people suffered with respiratory tract infections were above 60 is 174(48.3%) andminimum were 20-30 0f 12(3%).Conclusion: Our study concluded that most of the suffered with respiratory tract infections was mainlydue to the different types of lifestyle. It is treated with different types of drugs and the patients feel betterafter treatment. As a clinical pharmacist we should educate the patients regarding the health issues and theirproblem. It is most effective to educate the unemployed patient regarding the disease.
Keywords: pulmonology, clinical pharmacist, Estimation, Evaluation